Masa depan dimulai hari ini: Membangun kebiasaan positif pada anak TK - Katili, Kevin; Godwin, Danniel Tristano L.; Pertiwi, Dewi; Rahardjo, Richie Farandy (Penamas: Journal of Community Service, 2025)
This community service aims to introduce the concept of diligence and laziness to students of Bethel Sulung 3 Kindergarten, Surabaya, through an interactive approach designed to attract attention and facilitate student understanding. The methods include guessing games, education with puppet stages, coloring activities, and spelling and reading simple sentences. The guessing game involves classifying daily activities based on the concept of diligent and lazy, accompanied by explanations and collecting points as motivation. The puppet stage shows animal stories about diligence and laziness. Continued with a question and answer session to strengthen student understanding. Coloring activities using characters from the puppet storyline, ants and bees, to hone creativity and instill the value of hard work. Simple literacy, introducing new vocabulary about diligence and laziness, spelling exercises, and student reading. The data was obtained from observations and analysis of children’s work results, such as the number of points received and the quality of students’ coloring. Using methods in this interactive learning has proven effective in improving students’ understanding of the concept of diligent and lazy and motivating kindergarten students to participate in activities actively.